Constructions of Gender in Contemporary South African Crime Fiction: A Feminist Literary Analysis of the Novels of Angela Makholwa. Issue 2 (2nd July 2016) - Murray, Jessica
Abstract : This article offers a feminist literary analysis of Angela Makholwa's two crime novels, Red Ink (2007) and Black Widow Society (2013), in order to explore how a black female author represents gendered constructions of identity and gender violence in the genre of crime fiction. Over the last few decades, crime fiction has received increased scholarly attention in academic circles, both locally and abroad. In the South African context, scholars have tended to focus their analytical gaze on a few, well-known and established crime writers. I seek to extend the critical debate about South African crime writing by turning my attention to the work of a black female crime writer. Although Makholwa's novels make a number of observations about the salience of race in the South African milieu, this analysis focuses on her fictional representations of contemporary gender assumptions and relations. In particular, I consider how her literary representations of gender violence invite readers to trace the violence back to the gendered ordering of female characters' lived experiences. A close reading of her novels reveals that misogyny is rife and that, regardless of where they are located on the socio-economic ladder, female characters must negotiate their way in terms of very prescriptive and fundamentally gendered scripts. Rather than regarding violence against women as aberrations, these texts suggest that such violence is pervasive and that the brutal instances of physical violence are merely extreme manifestations of discursive and structural gender oppression that shapes every aspect of the female characters' lives. This article follows an interdisciplinary approach and I utilise founding and contemporary gender theory as well as sociological gender research to enrich the literary analysis of Makholwa's texts.